The prevalence and increasing trends of overweight, general obesity, and abdominal obesity among Chinese adults: a repeated cross-sectional study - Yongjie Chen; Qin Peng; Yu Yang; Senshuang Zheng; Yuan Wang; Wenli Lu (BMC, 2019)
Abstract Background The prevalence of general and abdominal obesity has increased rapidly in China. The aims of this study were to estimate the dynamic prevalence of overweight, general obesity, and abdominal obesity and the distribution of body mass index (BMI) and waist circumference (WC) among Chinese adults. Methods Data were obtained from the China Health and Nutrition Survey (CHNS). According to the suggestions of the WHO for Chinese populations, overweight was defined as a 23 kg/m2 ≤ BMI < 27.5 kg/m2 and general obesity as a BMI ≥ 27.5 kg/m2. Abdominal obesity was defined as a WC ≥ 90 cm for males and ≥ 80 cm for females. Grade 1, grade 2, and grade 3 obesity were defined as 27.5 kg/m2 ≤ BMI < 32.5 kg/m2, 32.5 kg/m2 ≤ BMI < 37.5 kg/m2, and BMI ≥ 37.5 kg/m2, respectively. Generalized estimation equations were used to estimate the prevalence and trends of overweight, general and abdominal obesity. Results This study included 12,543 participant. From 1989 to 2011, the median BMI of males and females increased by 2.65 kg/m2 and 1.90 kg/m2, respectively; and WC increased by 8.50 cm and 7.00 cm, respectively. In 2011, the age-adjusted prevalence of overweight, general obesity, and abdominal obesity were 38.80% (95% CI: 37.95-39.65%), 13.99% (95% CI: 13.38-14.59%), and 43.15% (95% CI: 42.28-44.01%), respectively, and significantly increased across all cycles of the survey among all subgroups (all P < 0.0001). The age-adjusted prevalence of grade 1-3 obesity significantly increased in total sample and sex subgroups (all P < 0.0001). For all indicators, there were significant increases in annual ORs among all subgroups (all P < 0.0001), with the exception of grade 2 obesity. Significant differences were observed in ORs across the three age groups in males. And ORs significantly decreased with age. Conclusions The age-adjusted prevalence of overweight, general obesity, and abdominal obesity significantly increased among Chinese adults from 1989 to 2011. The obesity population is trending toward an increased proportion of males and younger individuals in China.